A criança e os precursores da linguagem escrita: interações propulsoras do desenvolvimento simbólico na educação infantil - Faccienda, Mônica (2019)
The research that gave origin to this work had the objective of recognizing, in the daily life of Children's Education, the presence of the precursors of the written language, in order to understand the relation between the pretending play, the game and the design and the development of this modality of language, with reference to the meanings produced by the children and the didactic strategies that foment their symbolic development. What meanings do children elaborate during the pretending play, drawing and game activities? What do these productions say about the symbolic development of the child and the development of the written language? What didactic situations potentiate these manifestations? The study is based on the theoretical-methodological principles of the historical-cultural theory, especially in Vygotsky ’s (1995, 1998) and Luria’s works (2001) about the superior psychological functions and the symbolic development of the child. In a qualitative way, the research benefits from the methodological principles of the case study, using tools such as the observation, the interview and didactic interventions elaborated by the researcher. The field work was carried out at a public elementary school in Sarandi / RS, with three-year-old children. For the production of data, videotapes, field diary records, photographs and interviews were performed. Records produced by the children are also part of the collection, including drawings and writings. From the analysis, th e following conclusions were observed: the development of the symbolic capacities of the children depends on the relations that they experience and of what is offered to them, in the familiar and social context as in the school context; for the children to develop themselves symbolically, they must experience interactions in which the gestures, the playing and the drawings have meaning, in order they feel the necessity to learn more complex forms of representations, such as the writing; the achievement of these resources is an important condition for them to learn a new form of representation, more elaborated and complex, which will only make sense in the moment that the forms of representation used are insufficient to express their ideas, thoughts, feelings , learning or for the children’s communication; in the teaching planning of the Children’s Education teacher, it is possible to predict didactic situations which have that objective and which have associated the Children’s Literature, an important component for the exercise of the precursors of the writing.